STP Position Paper: Recommended Best Practices for Sampling, Processing, and Analysis of the Peripheral Nervous System (Nerves and Somatic and Autonomic Ganglia) during Nonclinical Toxicity Studies. (June 2018) - Bolon, Brad; Krinke, Georg; Butt, Mark T.; Rao, Deepa B.; Pardo, Ingrid D.; Jortner, Bernard S.; Garman, Robert H.; Jensen, Karl; Andrews-Jones, Lydia; Morrison, James P.; Sharma, Alok K.; Thibodeau, Michael S.
Peripheral nervous system (PNS) toxicity is surveyed inconsistently in nonclinical general toxicity studies. These Society of Toxicologic Pathology "best practice" recommendations are designed to ensure consistent, efficient, and effective sampling, processing, and evaluation of PNS tissues for four different situations encountered during nonclinical general toxicity (screening) and dedicated neurotoxicity studies. For toxicity studies where neurotoxicity is unknown or not anticipated (situation 1), PNS evaluation may be limited to one sensorimotor spinal nerve. If somatic PNS neurotoxicity is suspected (situation 2), analysis minimally should include three spinal nerves, multiple dorsal root ganglia, and a trigeminal ganglion. If autonomic PNS neuropathy is suspected (situation 3), parasympathetic and sympathetic ganglia should be assessed. For dedicated neurotoxicity studies where a neurotoxic effect is expected (situation 4), PNS sampling follows the strategy for situations 2 and/or 3, as dictated by functional or other compound/target-specific data. For all situations, bilateral sampling with unilateral processing is acceptable. For situations 1–3, PNS is processed conventionally (immersion in buffered formalin, paraffin embedding, and hematoxylin and eosin staining). For situation 4 (and situations 2 and 3 if resources and timing permit), perfusion fixation with methanol-free fixative is recommended. Where PNS neurotoxicity is suspected or likely, at least one (situations 2 and 3) or two (situation 4) nerve cross sections should be postfixed with glutaraldehyde and osmium before hard plastic resin embedding; soft plastic embedding is not a suitable substitute for hard plastic. Special methods may be used if warranted to further characterize PNS findings. Initial PNS analysis should be informed, not masked ("blinded"). Institutions may adapt these recommendations to fit their specific programmatic requirements but may need to explain in project documentation the rationale for their chosen PNS sampling, processing, and evaluation strategy.